hCG Priming Before Ovary Collection Increasing The Oocyte Quality In The Domestic Cat - Karisma Mardatillah; Rini Widyastuti; Diah Nugrahani Pristihadi; Wahyudin; Sigit Prastowo; Asep Gunawan; Arief Boediono (Acta VETERINARIA Indonesiana, 2021)
Oocyte competence is a determining factor that influences the embryo development. Embryos produced in vitro have a reduced developmental competence than embryos produced in vivo. Therefore, human Chorionic Gonadotropin (hCG) injection was carried out to improve the quality of the oocytes. The objective of this study was to evaluate the effect of ovarian stimulation with hCG before ovary collection on oocyte quality in the domestic cat. Oocyte donors were either 1) treated with a single dose of 200 IU hCG four days before ovary collection (hCG group), or, 2) no treatment before ovary collection (control group). The oocytes were collected by the slicing method. Immature cumulus oophorus complexes (COCs) from both groups were pooled and matured in vitro for 24-26 hours. Then mature oocytes were fertilized with epididymal sperm and cultured in vitro for seven days. The results study showed that the number of the dominant follicle (DF) and the number of COCs in the hCG group was higher than the control group in right and left ovaries (p<0.05). The morulae and blastocyst rates from cleavage embryos were 88% and 75%, respectively. These results demonstrate that hCG priming of oocytes donors before ovary collection improve oocyte quality.